PyKaldi: A Kaldi Wrapper in Python (International Journal of Innovative Research in Computer Science & Technology, 2022)
PyKaldi is much more than a set of Kaldi  library bindings. It offers best level of compatibility for  OpenFst classes with the tool “Kaldi” to make dealing with  Kaldi easier for Python users. PyKaldi is wrapper most  probably written in a language known as “Python” for the  widely used Kaldi SR toolkit that is free and open-source.  PyKaldi isn't only a set of Python bindings for Kaldi  libraries. It's a Python-based coding that lets programmers  or developers interact with OpenFst types or Kaldi in real  time. NumPy arrays are strongly integrated with both of the  tools discussed. PyKaldi, we hope, will substantially  improve the user experience and make integrating Kaldi  into Python processes much easier. PyKaldi has a lot of  documentation and testing. It supports Python 3 and also  the previous version 2, and is distributed under the Apache  License version 2.0. The fact that Kaldi has been so  efficacious should not arise as any wonder. The features  related to licence, rich documentation, tried methods for  developing cutting-edge systems, a big number of  international contributors, a devoted set of maintainers,  and, perhaps most significantly, a well-designed codebase  that is simple to comprehend, alter, and expand.
Keywords: CPython; Cython; Kaldi; OpenFst; PyKaldi; Python; Speech Recognition